2004
DOI: 10.1177/1082013204045882
|View full text |Cite
|
Sign up to set email alerts
|

Note: Antioxidant and Antibacterial Activities of Rosa Damascena Flower Extracts

Abstract: Rosa damascena Mill. is one of the most important Rosa species for the flavour and fragrance industries. The high amount of residues of spent flowers after steam distillation and the potential use of their essential oils as natural antioxidants and antimicrobials lead to determine the antioxidant and antibacterial activities of fresh and spent Rosa damascena flower extracts. The total phenolic contents were 276.02±2.93mg gallic acid equivalent (GAE)/g in FF (fresh flower) extract and 248.97±2.96mg GAE/g in SF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(109 citation statements)
references
References 24 publications
(26 reference statements)
5
100
1
3
Order By: Relevance
“…In addition to its perfuming effects, it was reported that the rose oil, rose flower extracts possessed a wide range of health beneficial activities, such as antibacterial 12,46,47 , antioxidant 13,14,48 , anti-infective and antiinflammatory properties 12,49 , anti-convulsant 50 and anti-HIV 11 . The extract of R. damascena induces the neurite outgrowth and inhibits the A β (25-35)-induce atrophy 51 .…”
Section: Rose Product and Its Usesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its perfuming effects, it was reported that the rose oil, rose flower extracts possessed a wide range of health beneficial activities, such as antibacterial 12,46,47 , antioxidant 13,14,48 , anti-infective and antiinflammatory properties 12,49 , anti-convulsant 50 and anti-HIV 11 . The extract of R. damascena induces the neurite outgrowth and inhibits the A β (25-35)-induce atrophy 51 .…”
Section: Rose Product and Its Usesmentioning
confidence: 99%
“…Rosa damascena has many culinary uses as a flavour additive. By-product of rose oil extraction can be utilized as an antioxidant and antibacterial agent in food industry 14 . Rose water and powdered roses are used in middle and eastern cooking.…”
Section: Rose Product and Its Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical properties of rose water have been reported to provide relief from toothache, aphthous lesions, and gingival and throat inflammation (Norman, 1963). It has been used as a remedy for gastrointestinal complications (Claus et al, 1970), acne (Sharma & Jain, 2013), bacterial infections (Ozkan et al, 2004), and gastric and duodenal spasms (Sharma & Jain, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…is an important Rosa species, which are known economically for their strong fragrance, oil production and their medicinal properties (Mahmood et al, 1996;Ardogan et al, 2002;Achuthan et al, 2003;Basim and Basim, 2003;Ozkan et al, 2004). In recent years, antioxidant, antibacterial and antimicrobial activities of essential oil R. damascena have been demonstrated (Achuthan et al, 2003;Ozkan et al, 2004). Antioxidants are compounds that can delay/inhibit the oxidation of lipids or other molecules by inhibiting the initiation or propagation of oxidative chain reactions (Velioglu et al, 1998) or alternatively scavenging the free radicals generated during oxidative destruction.…”
Section: Introductionmentioning
confidence: 99%